A comparative analysis of massed vs. distributed practice on basic math fact fluency growth rates. Issue 2 (April 2015) - Schutte, Greg M.; Duhon, Gary J.; Solomon, Benjamin G.; Poncy, Brian C.; Moore, Kathryn; Story, Bailey
Abstract To best remediate academic deficiencies, educators need to not only identify empirically validated interventions but also be able to apply instructional modifications that result in more efficient student learning. The current study compared the effect of massed and distributed practice with an explicit timing intervention to evaluate the extent to which these modifications lead to increased math fact fluency on basic addition problems. Forty-eight third-grade students were placed into one of three groups with each of the groups completing four 1-min math explicit timing procedures each day across 19 days. Group one completed all four 1-min timings consecutively; group two completed two back-to-back 1-min timings in the morning and two back-to-back 1-min timings in the afternoon, and group three completed one, 1-min independent timing four times distributed across the day. Growth curve modeling was used to examine the progress throughout the course of the study. Results suggested that students in the distributed practice conditions, both four times per day and two times per day, showed significantly higher fluency growth rates than those practicing only once per day in a massed format. These results indicate that combining distributed practice with explicit timing procedures is a useful modification that enhances student learning without the addition of extra instructional time when targeting math fact fluency.